Reactions of The First Cisplatin Hydrolytes cis-[PtCl(15NH3)2(H2O)]+ with N-Acetylcysteine - Sutopo Hadi (Jurnal Matematika & Sains, 2006)
The interactions between cis-[PtCl(15NH3)2(H2O)]+ and N-acetylcysteine (H3accys) in aqueous solution was investigated. In this reaction, polymeric solid was not formed and the amine liberation was slower than that of cis-[Pt(15NH3)2(H2O)2]2+. Initially, the only product observed in the reaction of cis-[PtCl(15NH3)2(H2O)]+ with a variety of thiols was a platinum(II) species with chloride and the thiolate ligand bound monodentate through sulphur, although different final product was obtained in each reaction. In this reaction, after the formation of a species with thiolate bound monodentate cis-[PtCl(15NH3)2(H2accys-S), two new platinum products were observed, namely a four-membered ring dinuclear platinum(II) complex, cis-[{Pt(15NH3)2)2}2( µ-Cl) ( µ-H2accys-S)]2+ and a six-membered -S,O- chelate ring complex, cis-[Pt(15NH3)2(Haccys-S,O), while dinuclear sulphur-bridged complex cis-[{Pt(NH3)2}2(H2accys- µ-S)2)]2+, giving a broad peak in 15N NMR, was only present in very tiny amounts in this reaction.